Faith in philosophy or philosophy within faith? - Peperzak, Adriaan T. (Budhi: a Journal of Ideas and Culture, 2014)
The question of the relationship between faith and philosophy opens a newpossibility for reading the history of philosophy. Despite modern thought’semancipation from religious and political authorities, philosophers fromDescartes to Kant and Hegel continued to see the connections between theirphilosophy and the Christian religion as a philosophical question of greatimportance, although religious practices or theological convictions no longeroccupied the center of their search for truth. In asking what kind of philosophyis compatible or incompatible with a philosopher’s attachment to Christianfaith, a retrieval of metaphorical and vocative language might open newpossibilities for interaction between philosophy and faith.